Method for producing organic sulfonic acid compound
By using a reaction matrix containing a chlorine-based compound in the manufacturing process of the organic sulfonic acid compound and combining the contacting process of anion and cation exchange resin, the problem of difficulty in reducing chloride ions and metal ions in the prior art has been successfully solved, and the production of high-purity organic sulfonic acid compounds has been achieved.
Patent Information
- Application Number
- CN202411415542.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-17
- Filing Date
- 2024-10-11
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to effectively reduce the concentration of chloride ions and metal ions in organic sulfonic acid compounds, and cannot meet the high purity requirements in the field of semiconductor manufacturing.
A manufacturing method including reaction step 1, contact step 2 and contact step 3 is adopted. In reaction step 1, the organic sulfonic acid compound is synthesized using a reaction matrix containing a chlorine compound. In the contacting step 2, a solution of the organic sulfonic acid compound is contacted with an anion exchange resin to adsorb chloride ions. In the contact step 3, the solution is contacted with the cation exchange resin to adsorb metal ions, and the two exchange resins are isolated from each other.
It effectively reduces the concentration of chloride ions and metal ions in organic sulfonic acid compounds, meets the high purity requirements in the field of semiconductor manufacturing, and avoids the problem of bubbles in the liquid flow during ion exchange.
Smart Images

Figure BDA0005079330570000111 
Figure BDA0005079330570000161
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application is based on Japanese Patent Application No. 2023-178683 filed with the Japan Patent Office on October 17, 2023, the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present invention relates to a method for producing an organic sulfonic acid compound. Background Art
[0004] In the technical field of manufacturing and precision processing of devices such as electronic components or semiconductors, high-performance cleaning agents containing surfactants are used. As examples of pollutants or attachments that may occur in the manufacturing process of silicon wafers or semiconductors, garbage or dust called particles and various impurity ions can be cited. Particles on semiconductors can cause malfunctions such as circuit disconnection. As a result, the semiconductor cannot be used. Therefore, the yield of the product will decrease. In addition, impurity ions such as chloride ions or metal ions on the metal wiring of the semiconductor may enter the gap between the metal wirings. At this time, the current leakage caused by the impurity ions may cause the semiconductor to malfunction. The presence of impurity ions may cause serious problems related to the manufactured device such as insufficient performance caused by changes in electrical characteristics, and further, chloride ions on the metal wiring of the semiconductor easily cause corrosion of the metal wiring to develop. As a result, it is easy to damage the metal wiring. Therefore, the resistance value of the metal wiring increases. In this way, the presence of particles or impurity ions has a significant impact on the quality of the semiconductor. In recent years, the miniaturization of devices such as smartphones and personal computers has been significant. The miniaturization of the semiconductors they use is also developing. The line width of the circuit of the miniaturized semiconductor is very thin. As a result, the smaller particles may cause deformation of the circuit, etc. Therefore, it is necessary to remove particles and impurity ions with higher precision. Therefore, a highly purified surfactant that further reduces the concentration of chloride ions and metal ions is required.
[0005] Regarding the purification method of the surfactant, in addition to the general concentration, crystallization or extraction method, for example, there is a known method of ion exchange method using ion exchange resin. For example, in the method disclosed in Japanese Patent Publication No. 2009-143842 (Patent Document 1), an alkali metal salt of an organic sulfonic acid is provided to an ion exchange method using a strongly acidic cation exchange resin. By treating with such an organic sulfonate, the concentration of various metal ions is reduced. In addition, in the method disclosed in Japanese Patent Publication No. 2015-38051 (Patent Document 2), an alkali metal salt and / or ammonium salt of an organic sulfonic acid is provided to an ion exchange method using a strongly acidic cation exchange resin. By treating with such an organic sulfonate, various metal ions are reduced. Furthermore, in the method disclosed in Japanese Patent Publication No. 2001-64249 (Patent Document 3), in order to reduce the content of sulfuric acid in alkanesulfonic acid, an aqueous solution of alkanesulfonic acid and a basic anion exchange resin are contacted with each other. Summary of the invention
[0006] However, when using general purification methods such as crystallization and extraction to reduce impurities, the quality of its surfactant is far from the quality required in the semiconductor field. In addition, according to the method disclosed in patent document 1 or patent document 2, the concentration of metal ions contained in the surfactant solution can be reduced. However, it is not clear whether the chloride ion concentration can be reduced by this method. According to the method disclosed in patent document 3, the concentration of sulfate ions contained in the surfactant solution can be reduced. However, it is not clear whether the chloride ion concentration or the metal ion concentration can be reduced by this method. In any patent document, it is not clear that chloride ions and metal ions are reduced to the quality required in the field of semiconductor manufacturing.
[0007] Surfactant solutions using organic sulfonic acid compounds are used in the manufacture of semiconductors, for example, for the purpose of dispersion, surface modification or cleaning. As a method for synthesizing organic sulfonic acid compounds, it is well known that there are methods for manufacturing using chlorine compounds and methods for manufacturing using sulfuric acid compounds. In the manufacturing method using chlorine compounds, many chloride ions from reactants such as chlorinated sulfonic acid are contained in the synthesized organic sulfonic acid. In the manufacturing method using sulfuric acid compounds, in most cases, a chlorine solvent such as chloroform is used as a solvent for the reaction. Therefore, chloride ions are contained in the synthesized sulfonic acid compound. In this way, in the manufacturing method using chlorine compounds, chloride ions from reactants such as chlorinated sulfonic acid are contained in the organic sulfonic acid compound. In addition, even in the manufacturing method using sulfuric acid compounds, when sodium salts are formed, chloride ions from impurities of the salt are more contained in the organic sulfonic acid compound. Therefore, the chloride ions become a problem in the field of semiconductor manufacturing. In such a case, it is desired to reduce these chloride ions.
[0008] Therefore, the present disclosure provides a method for producing an organic sulfonic acid compound capable of effectively reducing the chloride ion content and the metal ion content.
[0009] The method for producing an organic sulfonic acid compound according to an embodiment of the present disclosure includes a reaction step 1, a contact step 2, and a contact step 3, wherein in the reaction step 1, the organic sulfonic acid compound is synthesized using a reaction substrate containing a chlorine-based compound, in the contact step 2, the solution of the organic sulfonic acid compound obtained in the reaction step 1 is contacted with an anion exchange resin, and in the contact step 3, the solution of the organic sulfonic acid compound after the contact step 2 is contacted with a cation exchange resin, and the anion exchange resin in the contact step 2 and the cation exchange resin in the contact step 3 are isolated from each other.
[0010] In the following detailed description, for purposes of explanation, numerous specific details are set forth in order to provide a thorough understanding of the disclosed embodiments. However, it will be apparent that one or more embodiments may be practiced without these specific details.
[0011] In order to solve the above-mentioned problems, the technology disclosed in the present invention includes the following means.
[0012] (1) A method for producing an organic sulfonic acid compound, comprising a reaction step 1, a contact step 2, and a contact step 3, wherein the organic sulfonic acid compound is synthesized using a reaction substrate containing a chlorine-based compound in the reaction step 1, the organic sulfonic acid compound solution obtained in the reaction step 1 is contacted with an anion exchange resin in the contact step 2, and the organic sulfonic acid compound solution after the contact step 2 is contacted with a cation exchange resin in the contact step 3, and the anion exchange resin in the contact step 2 and the cation exchange resin in the contact step 3 are isolated from each other.
[0013] (2) The production method according to (1), wherein the organic sulfonic acid compound is a surfactant.
[0014] (3) The production method according to (1), wherein in the contact step 2, the solution having an organic sulfonic acid compound concentration of 1 to 50% by mass is contacted with the anion exchange resin.
[0015] (4) The production method according to (1), wherein in the contact step 3, the solution having an organic sulfonic acid compound concentration of 1 to 40% by mass is contacted with the cation exchange resin.
[0016] (5) The production method according to (1), wherein in the contacting step 2, the solution is contacted at a space velocity (SV) of 0.3 to 4.9 h -1 Contact with the above anion exchange resin.
[0017] (6) The production method according to (1), wherein in the contacting step 3, the solution is contacted at a space velocity (SV) of 0.3 to 4.9 h -1 Contact with the above-mentioned cation exchange resin. DETAILED DESCRIPTION
[0018] In the description of the present embodiment, unless otherwise specified, the numerical range represented by "A to B" includes the upper and lower limits thereof. That is, "A to B" means "A or more and B or less".
[0019] According to the production method of the present disclosure described above, it is possible to provide a method for producing an organic sulfonic acid compound that can efficiently reduce the chloride ion content and the metal ion content.
[0020] The method for producing an organic sulfonic acid compound of the present embodiment includes a reaction step 1 for synthesizing an organic sulfonic acid compound, a contact step 2 for performing ion exchange, and a contact step 3. Here, the ion exchange resin in the contact step 2 and the ion exchange resin in the contact step 3 are separated from each other.
[0021] Reaction process 1
[0022] In reaction process 1, the organic sulfonic acid compound is synthesized using a reaction matrix containing a chlorine compound. In the present embodiment, "reaction matrix containing a chlorine compound" refers to a series of reaction matrices contained in the starting material of reactions such as solvents or catalysts. As examples of reaction matrices, aromatic hydrocarbons containing benzene, octylbenzene, dodecylbenzene and octadecylbenzene and unsaturated hydrocarbons containing double bonds including octene, decene, undecene, dodecene, tetradecene, hexadecene and octadecene can be cited. Among these, preferably benzene, dodecylbenzene, octene, dodecene, hexadecene and octadecene. One of these reaction matrices can be used alone. Alternatively, the reaction matrix of more than 2 can be combined and used.
[0023] (Chlorine compounds)
[0024] The chlorine compound used is not particularly limited. Examples of chlorine compounds include sodium chloride, potassium chloride, calcium chloride, magnesium chloride, ammonium chloride, aluminum chloride, hydrogen chloride, ferric chloride, cupric chloride, methyl chloride, ethyl chloride, chlorosulfonic acid, chloroform, and chlorobenzene. One of these chlorine compounds may be used alone. Alternatively, two or more chlorine compounds may be used in combination.
[0025] (Organic sulfonic acid compound)
[0026] The synthesis method of reaction step 1 is not particularly limited. A conventionally known method can be used. Examples of the synthesis method include a sulfonation method using a chlorine compound, a sulfonation reaction using a sulfuric acid compound, or a sulfonation reaction using sulfur dioxide and oxygen followed by neutralization with sodium hydroxide. The synthesized organic sulfonic acid compound may be any of a monosulfonic acid compound, a disulfonic acid compound, and a mixture thereof. In addition, the alkyl group contained in the organic sulfonic acid compound includes a straight-chain alkyl group and a branched-chain alkyl group. The number of carbon atoms in the alkyl group may be distributed.
[0027] The organic sulfonic acid compound is preferably a surfactant. Examples of such organic sulfonic acid compounds include sodium octyl sulfonate, sodium dodecylbenzene sulfonate, and sodium octadecyl sulfonate. However, the surfactant that can be used is not limited to these examples.
[0028] In the reaction step 1, a halogen (chlorine-containing compound) is generated as a by-product while the organic sulfonic acid compound is generated. Alternatively, chlorine from the chlorine-based compound used as a solvent for the reaction is contained in the organic sulfonic acid compound. Therefore, in order to purify the synthesized organic sulfonic acid compound, the following contact steps 2 and 3 are performed in sequence.
[0029] Contact process 2
[0030] In the contact process 2, the solution of the organic sulfonic acid compound obtained in the reaction process 1 is contacted with an anion exchange resin. The purpose of the contact process 2 is mainly to adsorb the chloride ions in the organic sulfonic acid compound to the anion exchange resin. In the contact process 2 and the contact process 3 described later, the method for contacting the solution of the organic sulfonic acid compound with the ion exchange resin is not particularly limited. For example, a column method or an intermittent method can be used. From the viewpoint of operating efficiency, etc., a column method is preferred. According to the method disclosed in the present invention, a known device such as an ion exchange column can be used to contact it with the ion exchange resin.
[0031] The solution of the organic sulfonic acid compound obtained in the reaction step 1 is passed through an anion exchange resin. As a result, the chloride ions contained in the solution of the organic sulfonic acid compound are adsorbed on the anion exchange resin. As a result, the chloride ion concentration in the purified liquid obtained can be reduced. In the present disclosure, the contact step 2 is performed after the reaction step 1. That is, from the organic sulfonic acid compound in the state of being synthesized in the reaction step 1, by performing anion exchange in the contact step 2, only the chloride ions are selectively captured in the anion exchange resin. As a result, the chloride ion concentration can be effectively reduced. It should be noted that the solution of the organic sulfonic acid compound is a solution obtained by dissolving the organic sulfonic acid compound synthesized in the reaction step 1 in a solvent suitable for the ion exchange method, such as ion exchange water.
[0032] (Anion Exchange Resin)
[0033] The anion exchange resin used in the contact step 2 may be any one of a strongly basic resin, a weakly basic resin, and a mixed resin thereof. Among these, an anion exchange resin containing a strongly basic anion exchange resin is preferred. The anion exchange resin used is not particularly limited. Known anion exchange resins may be used. The shape of the anion exchange resin is not limited to granular. The shape of the resin may also be powdery, fibrous, or film-like. The structure of the anion exchange resin may be a gel type or a macroporous type. One of these anion exchange resins may be used alone. Alternatively, two or more anion exchange resins may be used in combination.
[0034] The ratio of the content of the strongly basic anion exchange resin contained in the anion exchange resin is not particularly limited. The preferred content ratio is 50% by volume or more. When the content ratio of the strongly basic anion exchange resin is within this range, the chloride ion content in the solution of the organic sulfonic acid compound is effectively reduced because the chloride ions are adsorbed on the strongly basic anion exchange resin.
[0035] Strongly basic anion exchange resin refers to an anion exchange resin into which a strongly basic functional group such as a quaternary ammonium base (R-N+R1R2R3) is introduced. Examples of strongly basic anion exchange resins that can be used include Amberlite (registered trademark, the same below) "IRA400J Cl, IRA402BL and IRA900J (all manufactured by Dupont, USA)", Duolite (registered trademark, the same below) "A113LF, A161JCL and AGP (all manufactured by Dupont, USA)", and Diaion (registered trademark, the same below) "SA10A and SA11A (both manufactured by Mitsubishi Chemical Corporation)" type I strongly basic anion exchange resins. In addition, as other examples, there can be mentioned type II strong basic anion exchange resins including Amberlite "IRA410J, IRA910CT and HPR4010 (all manufactured by Dupont, USA)", Duolite "A116 and A162LF (both manufactured by Dupont, USA)", and Diaion "SA20A and SA20ALL (both manufactured by Mitsubishi Chemical Corporation)".
[0036] Weakly basic anion exchange resins are anion exchange resins into which weakly basic functional groups such as primary to tertiary amines are introduced. Examples of weakly basic anion exchange resins include Amberlite "IRA67, IRA96SB and IRA98 (all manufactured by Dupont, USA)", Duolite "A368MS, A378D and A375LF (all manufactured by Dupont, USA)" and Diaion "WA10 and WA20 (both manufactured by Mitsubishi Chemical Corporation)".
[0037] It is preferred that the anion exchange resin be regenerated to the OH form in advance using a salt such as an aqueous solution of tetramethylammonium salt. The obtained OH form anion exchange resin is thoroughly washed with, for example, ion exchange water or ultrapure water.
[0038] In the contact step 2, the concentration of the organic sulfonic acid compound in the solution of the organic sulfonic acid compound in contact with the anion exchange resin is not particularly limited. The preferred concentration is 1 to 50% by mass. When the concentration of the solution is too high, the viscosity of the solution becomes high. Therefore, the molecular motion in the solution is restricted. As a result, the number of contacts between the ion exchange resin and the chloride ions is reduced, and it is difficult to effectively reduce the chloride ion concentration.
[0039] The concentration of the organic sulfonic acid compound in the solution of the organic sulfonic acid compound in contact with the anion exchange resin is more preferably 15 to 35% by mass. When the concentration is too low, the amount of water used for dilution increases. Therefore, the flow rate of the organic sulfonic acid compound solution per unit time during ion exchange must be increased. Therefore, from the perspective of productivity, too low a concentration is not appropriate.
[0040] The space velocity (SV) when the solution of the organic sulfonic acid compound is subjected to ion exchange treatment in the contact step 2 is preferably set to 0.3 to 4.9 h -1 , more preferably 0.3 to 1.0 h -1 If the speed of passing the liquid is too fast, it is difficult to fully adsorb the chloride ions. It should be noted that the space velocity (SV) value is a unit that expresses how many times the amount of treated water is passed per hour relative to the amount of ion exchange resin filled.
[0041] Contact process 3
[0042] In the contact step 3, the solution of the organic sulfonic acid compound that has passed through the contact step 2 is contacted with a cation exchange resin. The purpose of the contact step 3 is mainly to adsorb the chloride ions in the organic sulfonic acid compound to the cation exchange resin. When the solution of the organic sulfonic acid compound that has passed through the contact step 2 passes through the cation exchange resin, the metal ions contained in the solution of the organic sulfonic acid compound are adsorbed to the cation exchange resin. As a result, not only the chloride ions in the obtained purified solution can be reduced, but also the metal ions can be reduced.
[0043] (Cation Exchange Resin)
[0044] The cation exchange resin used in the contact step 3 may be any one of a strongly acidic resin, a weakly acidic resin, and a mixed resin thereof. Of these, a cation exchange resin containing a strongly acidic cation exchange resin is preferred. The cation exchange resin used is not particularly limited. Known cation exchange resins may be used. The shape of the cation exchange resin is not limited to granular. The shape of the resin may also be powdery, fibrous, or film-like. The structure of the cation exchange resin may be a gel type or a macroporous type. One of these cation exchange resins may be used alone. Alternatively, a combination of two or more cation exchange resins may be used.
[0045] The ratio of the content of the strongly acidic cation exchange resin contained in the cation exchange resin is not particularly limited. The preferred content ratio is 90% by volume or more. When the ratio of the content of the strongly acidic cation exchange resin is within this range, the metal ion content in the solution of the organic sulfonic acid compound is effectively reduced because the metal ions are adsorbed on the strongly acidic cation exchange resin.
[0046] Strong acid cation exchange resin refers to a cation exchange resin with a large adsorption force for cationic components. Strong acid cation exchange resin has a strong acid exchange group such as sulfonic acid group (R-SO3-H+) as a functional group. Examples of strong acid cation exchange resins that can be used include Amberlite IR120BNa, IR-124Na and 200CTNa (all made by Dupont, USA); Duolite C20, C20LF and C255LFH (all made by Dupont, USA); and Diaion SK104H, SK110 and SK1B (all made by Mitsubishi Chemical Corporation).
[0047] Weakly acidic cation exchange resins are cation exchange resins with a relatively small adsorption force for cationic components. Weakly acidic cation exchange resins have a weakly acidic exchange group such as a carboxylic acid group (R-COO-H+) as a functional group. Examples of weakly acidic cation exchange resins that can be used include Amberlite IRC76, FPC3500, and HPR8400 (all manufactured by Dupont, USA); Duolite C476 (manufactured by Dupont, USA); and Diaion WK10 and WK11 (both manufactured by Mitsubishi Chemical Corporation).
[0048] The cation exchange resin is preferably regenerated in advance to the H-type using an acid such as hydrochloric acid or sulfuric acid. The obtained H-type cation exchange resin is thoroughly washed with, for example, ion exchange water or ultrapure water.
[0049] In the contact step 3, the concentration of the organic sulfonic acid compound in the solution of the organic sulfonic acid compound in contact with the cation exchange resin is not particularly limited. The preferred concentration is 1 to 40% by mass. When the concentration of the solution is too high, the viscosity of the solution becomes high. Therefore, the molecular motion in the solution is restricted. As a result, the number of contacts between the ion exchange resin and the metal ions is reduced, and it is difficult to effectively reduce the concentration of the metal ions.
[0050] The concentration of the organic sulfonic acid compound in the solution of the organic sulfonic acid compound in contact with the cation exchange resin is more preferably 15 to 30% by mass. When the concentration is too low, the amount of water used for dilution increases. Therefore, the flow rate of the organic sulfonic acid compound solution per unit time during ion exchange must be increased. Therefore, from the perspective of productivity, too low a concentration is not appropriate.
[0051] The space velocity (SV) when the solution of the organic sulfonic acid compound is subjected to ion exchange treatment in the contact step 3 is preferably set to 0.3 to 4.9 h -1 , more preferably 0.3 to 1.0 h -1 If the liquid is passed through too fast, it is difficult to fully adsorb the metal ions.
[0052] In this embodiment, the reaction step 1, the contact step 2 and the contact step 3 are sequentially performed. Thus, an organic sulfonic acid compound is produced. In the reaction step 1, a reaction substrate containing a chlorine compound is used to synthesize the organic sulfonic acid compound. In the contact step 2, an anion exchange resin is used to perform anion exchange, and only chloride ions are selectively captured in the anion exchange resin from the organic sulfonic acid compound in the synthesized state. Then, in the contact step 3, by performing cation exchange using a cation exchange resin, metal ions can be removed from the solution of the organic sulfonic acid compound in the state of having passed the contact step 2. Therefore, as a result of purification, an organic sulfonic acid compound with reduced concentrations of chloride ions and metal ions can be obtained.
[0053] On the other hand, when the contact step 2 and the contact step 3 are carried out in the reverse order, in the reaction step 1, the organic sulfonic acid compound in the state of being synthesized using the reaction substrate containing the chlorine compound is subjected to cation exchange in the contact step 3. Therefore, in the cation exchange in the contact step 3, when the metal ions are adsorbed to the cation exchange resin, the organic sulfonic acid compound becomes an organic alkyl sulfonic acid. Then, when the anion exchange is carried out in the contact step 2, the chloride ions are adsorbed to the anion exchange resin. At this time, the sulfonic acid is also adsorbed by the anion exchange. Therefore, as a result of purification, the organic sulfonic acid compound from which the chloride ions and the metal ions are removed cannot be obtained.
[0054] Furthermore, in this embodiment, the anion exchange resin in the contact step 2 and the cation exchange resin in the contact step 3 are isolated from each other. On the other hand, when the anion exchange resin contacts the cation exchange resin, carbonate ions and protons are generated in the contact portion. That is, the anion exchange resin contacts the air and adsorbs carbon dioxide. Then, the carbonate ions are freed from the anion exchange resin. Then, the free carbonate ions react with the protons (H) generated by the cation exchange resin. + ) contact. As a result, carbon dioxide bubbles are generated. Therefore, the solution of the organic sulfonic acid compound becomes difficult to pass through. As a result, ion exchange is not fully performed. In addition, in the case of using a mixed resin of an anion exchange resin and a cation exchange resin to carry out the contact step 2 and the contact step 3, carbon dioxide bubbles are also generated in the same manner. As a result, ion exchange is not fully performed.
[0055] According to the manufacturing method described above, an organic sulfonic acid compound with reduced concentrations of chloride ions and metal ions can be obtained. Moreover, it is also possible to avoid the situation where ion exchange is not performed due to, for example, bubbles being generated during the liquid flow. As a result, a high-purity organic sulfonic acid compound can be efficiently manufactured.
[0056] Example
[0057] Hereinafter, the operation and effect of the present embodiment will be described in more detail by way of examples and comparative examples. However, the present embodiment is not limited to these examples. In the following examples and comparative examples, % refers to mass %. Table 1 shows the compounds synthesized in the reaction step 1 in each example and each comparative example and their synthesis methods. Furthermore, Table 1 shows the solution concentrations, SV values and test methods of the contact steps 2 and 3, respectively.
[0058] Reaction process 1
[0059] In reaction step 1, the following synthesis methods 1 to 3 were performed. In Examples 1 to 5, 7 to 10, and 14 to 31, and Comparative Examples 1 to 5, synthesis method 1 was performed. In Example 6, synthesis method 2 was performed. In Example 32, synthesis method 3 was performed. In Examples 11 to 13, synthesis methods 1 and synthesis methods 3 were performed.
[0060] Example 1
[0061] (Synthesis Method 1)
[0062] 116.5 g (1.0 mol, 1.0 eq.) of chlorosulfonic acid was added dropwise to a 500 mL four-necked flask weighing 246.4 g (1.0 mol) of dodecylbenzene over 10 minutes. After the addition, the mixture was heated to 150°C. Then, the reaction was carried out for 10 hours. The above reactants were added to a 2 L beaker weighing 500 g of water. The reaction mixture was stirred at 70°C for 2 hours and then cooled. Next, a 30 wt% aqueous sodium hydroxide solution was added to reach a neutral region. In this way, an aqueous solution of sodium dodecylbenzene sulfonate was recovered as a reaction product. Then, water and unreacted dodecylbenzene were removed by vacuum distillation of the obtained aqueous solution. From the obtained solid, chloroform was removed by vacuum distillation from the organic layer obtained by extraction using chloroform. Thus, sodium dodecylbenzene sulfonate from which impurities were removed was obtained.
[0063] Examples 2 to 5, 7 to 10, 14 to 31, Comparative Examples 1 to 5
[0064] The sulfonic acid compounds shown in Table 1 were obtained by the same method as in Synthesis Method 1 except that the reaction substrate of Synthesis Method 1 was changed from dodecylbenzene to an unsaturated hydrocarbon (C8-C18) containing a double bond.
[0065] Example 6
[0066] (Synthesis Method 2)
[0067] 113.4 g (1.2 mol, 1.0 eq.) of 20% fuming sulfuric acid was added dropwise to a 500 mL four-necked flask weighing 295.7 g (1.2 mol) of dodecylbenzene over 10 minutes. After the addition, the mixture was heated to 160°C. Then, the reaction was carried out for 4 hours. The above reactants were added to a 2 L beaker weighing 700 g of water. The reaction mixture was stirred at 70°C for 2 hours and then cooled. Next, a 30 wt% aqueous sodium hydroxide solution was added to reach the neutral region. In this way, an aqueous solution of sodium dodecylbenzene sulfonate was recovered as a reaction product. Then, water and unreacted dodecylbenzene were removed by vacuum distillation of the obtained aqueous solution. From the obtained solid, chloroform was removed by vacuum distillation from the organic layer obtained by extraction using chloroform. Thus, sodium dodecylbenzene sulfonate from which impurities were removed was obtained.
[0068] Embodiment 11
[0069] Sodium dodecylbenzenesulfonate was obtained by Synthesis Method 1. Sodium dodecylbenzene disulfonate was obtained by the following Synthesis Method 3. The sulfonic acid compound of Example 11 was prepared at a ratio of sodium dodecylbenzenesulfonate / sodium dodecylbenzene disulfonate = 9:1.
[0070] (Synthesis Method 3)
[0071] 226.7 g (2.4 mol, 2.0 eq.) of 20% fuming sulfuric acid was added dropwise to a 500 mL four-necked flask weighing 295.7 g (1.2 mol) of dodecylbenzene over 10 minutes. After the addition, the mixture was heated to 160°C. Then, the reaction was carried out for 4 hours. The above reactants were added to a 2 L beaker weighing 700 g of water. The reaction mixture was stirred at 70°C for 2 hours and then cooled. Next, a 30 wt% aqueous sodium hydroxide solution was added to reach a neutral region. In this way, an aqueous solution of sodium dodecylbenzene disulfonate was recovered as a reaction product. Then, water and unreacted dodecylbenzene were removed by vacuum distillation of the obtained aqueous solution. From the obtained solid, chloroform was removed by vacuum distillation from the organic layer obtained by extraction using chloroform. Thus, sodium dodecylbenzene disulfonate from which impurities were removed was obtained.
[0072] Embodiment 12, 13
[0073] The sodium alkyl (C10-C18) sulfonate of Example 12 and the sodium tetradecyl sulfonate of Example 13 were obtained by the same method as in Synthesis Method 1, except that the reaction substrate of Synthesis Method 1 was changed from dodecylbenzene to an unsaturated hydrocarbon (C10-C18) containing a double bond. The sodium alkyl (C10-C18) disulfonate of Example 12 and the tetradecyl disulfonic acid of Example 13 were obtained by the same method as in Synthesis Method 3, except that the reaction substrate of Synthesis Method 3 was changed from dodecylbenzene to an unsaturated hydrocarbon (C10-C18) containing a double bond.
[0074] The sulfonic acid compound of Example 12 was prepared at a ratio of sodium alkyl (C10-C18) sulfonate: sodium alkyl (C10-C18) disulfonate = 1:9. The sulfonic acid compound of Example 13 was prepared at a ratio of sodium tetradecyl sulfonate: sodium tetradecyl disulfonate = 1:1.
[0075] Embodiment 32
[0076] Sodium benzene disulfonate was obtained by the same method as in Synthesis Method 3 in Example 11 except that the reaction substrate of Synthesis Method 3 was changed from dodecylbenzene to benzene.
[0077]
[0078] The sulfonic acid compound synthesized in the reaction step 1 was diluted with water to generate an aqueous solution of an organic sulfonic acid compound. The concentration of the organic sulfonic acid compound in the obtained aqueous solution is shown in Table 1. Then, the contact step 2 and the contact step 3 were sequentially performed.
[0079] Contact process 2
[0080] In the contacting step 2, the following test methods 2-1 to 2-6 were performed. In Examples 1 to 13, 15, 17 to 28, and 31 to 32, and Comparative Example 3, the test method 2-1 was performed. In Examples 14 and 16, the test method 2-2 was performed. In Example 29, the test method 2-3 was performed. In Example 30, the test method 2-4 was performed. In Comparative Example 4, the test method 2-5 was performed. In Comparative Example 5, the test method 2-6 was performed. In Comparative Example 2, the test method 3-1 described later was performed.
[0081] (Test method 2-1)
[0082] A column with a content of 300 ml set vertically was filled with 200 ml of a gel-type strongly basic anion exchange resin (trade name "Amberlite IRA400J Cl"). Here, the strongly basic anion exchange resin was regenerated to OH type using a 1N tetramethylammonium hydroxide aqueous solution in advance. The anion exchange resin was fully washed with 4000 g of pure water and then allowed to stand for 24 hours. Next, the pure water injected into the column was maintained at a constant temperature within the range of 15 to 25°C. Then, an aqueous solution of an organic sulfonic acid compound adjusted to the same temperature as the pure water in the column was circulated at the space velocity (SV) described in Table 1.
[0083] (Test method 2-2)
[0084] The aqueous solution of the organic sulfonic acid compound was circulated at the space velocity (SV) shown in Table 1 in the same manner as in Test Method 2-1 except that the gel-type strong base anion exchange resin (trade name “Amberlite IRA400JCl”) in Test Method 2-1 was replaced with an MR-type strong base anion exchange resin (trade name “Amberlite IRA900J”).
[0085] (Test Method 2-3)
[0086] The aqueous solution of the organic sulfonic acid compound was circulated at the space velocity (SV) shown in Table 1 in the same manner as in Test Method 2-1 except that the gel-type strong basic anion exchange resin (trade name “Amberlite IRA400JCl”) in Test Method 2-1 was replaced with a gel-type weak basic anion exchange resin (trade name “Amberlite IRA67”).
[0087] (Test methods 2-4)
[0088] 100 ml of the gel-type strong basic anion exchange resin (trade name "Amberlite IRA400JCl") of Test Method 2-1 and 100 ml of the gel-type weak basic anion exchange resin (trade name "Amberlite IRA67") of Test Method 2-3 are uniformly mixed. Fill a vertically arranged column with a content of 300 ml with the above mixed resin. Next, the pure water injected into the column is maintained at a constant temperature in the range of 15 to 25°C. Then, an aqueous solution of an organic sulfonic acid compound adjusted to the same temperature as the pure water in the column is circulated at the space velocity (SV) described in Table 1.
[0089] (Test methods 2-5)
[0090] 100 ml of MR type strong acid cation exchange resin (trade name "Amberlite200CT") was regenerated into H type using 1N dilute hydrochloric acid. In addition, 100 ml of MR type strong base anion exchange resin (trade name "Amberlite IRA900J") was regenerated into OH type using 1N tetramethylammonium hydroxide aqueous solution. Then, the regenerated cation exchange resin and anion exchange resin were evenly mixed. A vertically arranged column with a content of 300 ml was filled with the above mixed resin. Next, the pure water injected into the column was maintained at a constant temperature in the range of 15 to 25°C. Then, an aqueous solution of an organic sulfonic acid compound adjusted to the same temperature as the pure water in the column was circulated at the space velocity (SV) described in Table 1.
[0091] (Test Methods 2-6)
[0092] A vertically arranged column with a content of 300 ml is filled with 100 ml of MR type strong basic anion exchange resin (trade name "Amberlite IRA900J"). Next, the column is filled with 100 ml of MR type strong acid cation exchange resin (trade name "Amberlite 200CT") which has been regenerated to H type using 1N dilute hydrochloric acid in advance. At this time, the anion exchange resin and the cation resin located above it are in contact with each other in the column. Next, the pure water injected into the column is maintained at a constant temperature in the range of 15 to 25°C. Then, an aqueous solution of an organic sulfonic acid compound adjusted to the same temperature as the pure water in the column is circulated at the space velocity (SV) described in Table 1.
[0093] Contact process 3
[0094] In the contact step 3, the following test methods 3-1 to 3-3 were performed. In Examples 1 to 14, 17 to 30 and 32 and Comparative Example 1, the test method 3-1 was performed. In Examples 15 and 16, the test method 3-2 was performed. In Example 31, the test method 3-3 was performed. In Comparative Example 2, the test method 2-1 of the contact step 2 was performed.
[0095] (Test method 3-1)
[0096] Fill a vertically arranged column with a content of 300 ml with 200 ml of a gel-type strongly acidic cation exchange resin (trade name "Amberlite IR-124Na") that was previously regenerated to H-type using 1N dilute hydrochloric acid. Use 4000 g of pure water to thoroughly wash the cation exchange resin, and then let it stand for 24 hours. Next, maintain the pure water injected into the column at a constant temperature in the range of 15 to 25°C. Then, circulate the aqueous solution of the organic sulfonic acid compound adjusted to the same temperature as the pure water in the column at the space velocity (SV) described in Table 1.
[0097] (Test method 3-2)
[0098] The aqueous solution of the organic sulfonic acid compound was circulated at the space velocity (SV) described in Table 1 in the same manner as in Test Method 3-1, except that the gel-type strongly acidic cation exchange resin (trade name "Amberlite IR-124Na") in Test Method 3-1 was replaced with an MR-type strongly acidic cation exchange resin (trade name "Amberlite 200CT").
[0099] (Test method 3-3)
[0100] Evenly mix 180 ml of the gel-type strong acid cation exchange resin (trade name "Amberlite IR-124Na") of Test Method 3-1 and 20 ml of the MR-type weak acid cation exchange resin (trade name "Amberlite FPC3500"). Fill a vertically arranged column with a content of 300 ml with the above mixed resin. Next, maintain the pure water injected into the column at a constant temperature in the range of 15 to 25°C. Then, circulate an aqueous solution of an organic sulfonic acid compound adjusted to the same temperature as the pure water in the column at the space velocity (SV) described in Table 1.
[0101] The chlorine content, each metal content, and the amount of purification per unit time of the aqueous solutions of the organic sulfonic acid compounds obtained in Examples 1 to 32 and Comparative Examples 1 to 5 were measured and evaluated by the following test methods. Table 2 shows the results.
[0102] Chlorine content
[0103] The chloride ion content in the aqueous solution of the purified organic sulfonic acid compound was quantitatively determined by dropping a 0.01 mol / l silver nitrate aqueous solution using a potentiometric titrator (AT-610, manufactured by Kyoto Electronics Co., Ltd.) The chloride ion content in the aqueous solution of the purified organic sulfonic acid compound was evaluated according to the following evaluation criteria.
[0104] (Evaluation criteria for chloride ions (values based on aqueous solution))
[0105] A: Chloride ion content is less than 20ppm (excellent)
[0106] B: Chloride ion content is 20 ppm or more and less than 50 ppm (good)
[0107] C: Chloride ion content is 50 ppm or more and less than 100 ppm (qualified)
[0108] D: Chloride ion content is more than 100ppm (unqualified)
[0109] Metal content
[0110] The metal ion content in the aqueous solution of the purified organic sulfonic acid compound was measured using an inductively coupled plasma mass spectrometer (ICP-MS 7700, manufactured by Agilent Technologies Inc.) The content of each metal ion in the aqueous solution of the purified organic sulfonic acid compound was evaluated according to the following evaluation criteria.
[0111] (Evaluation criteria of Na ions (values based on aqueous solution))
[0112] A: Na ion content is less than 30ppb (excellent)
[0113] B: Na ion content is 30 ppb or more and less than 50 ppb (good)
[0114] C: Na ion content is 50 ppb or more and less than 80 ppb (qualified)
[0115] D: Na ion content is above 80ppb (unqualified)
[0116] (Evaluation criteria of K ions (values based on aqueous solution))
[0117] A: K ion content is less than 5ppb (excellent)
[0118] B: K ion content is 5 ppb or more and less than 20 ppb (good)
[0119] C: K ion content is 20 ppb or more and less than 50 ppb (qualified)
[0120] D: K ion content is above 50ppb (unqualified)
[0121] (Evaluation criteria of Ca ions (values based on aqueous solution))
[0122] A: Ca ion content is less than 10ppb (excellent)
[0123] B: Ca ion content is 10 ppb or more and less than 20 ppb (good)
[0124] C: Ca ion content is 20 ppb or more and less than 50 ppb (qualified)
[0125] D: Ca ion content is above 50ppb (unqualified)
[0126] (Evaluation criteria of Fe ions (values based on aqueous solution))
[0127] A: Fe ion content is less than 10ppb (excellent)
[0128] B: Fe ion content is 10 ppb or more and less than 20 ppb (good)
[0129] C: Fe ion content is 20 ppb or more and less than 50 ppb (qualified)
[0130] D: Fe ion content is 50 ppb or more (unqualified)
[0131] Purification volume per unit time
[0132] The purification amount per hour in the contact step 2 and the contact step 3 was measured in terms of solid content per 100 ml of the ion exchange resin. The measured purification amount was evaluated based on the following evaluation criteria.
[0133] A: Purification amount is 10 g or more (excellent)
[0134] B: The purified amount is 5 g or more and less than 10 g (good)
[0135] C: Purification amount is less than 5g (qualified)
[0136] Table 2
[0137]
[0138] In Examples 1 to 32, the chloride ion content in the aqueous solution of the purified organic sulfonic acid compound was reduced to less than 100 ppm. Regarding the metal contents, the Na ion content was reduced to less than 80 ppb. The K ion content, the Ca ion content, and the Fe ion content were reduced to less than 50 ppb. Furthermore, in Examples 1 to 19, 21 to 32, the purification amount per unit time in any of the contact process 2 and the contact process 3 was 5 g or more. In Example 20, in any of the contact process 2 and the contact process 3, the concentration of the solution of the organic sulfonic acid compound contacted with the exchange resin was low. Therefore, the purification amount per unit time did not exceed 5 g. However, the evaluation of the chloride ion content and the content of each metal was excellent. On the other hand, in Comparative Example 1, the contact process 2 was not performed. Therefore, the chloride ion content was 100 ppm or more. In Comparative Example 2, after the contact process 3, the contact process 2 was performed. Therefore, the chloride ion content was 100 ppm or more. In Comparative Example 3, the contact process 3 was not performed. Therefore, the content of each metal ion was not sufficiently reduced. In Comparative Example 4, a mixed bed of anion exchange resin and cation exchange resin was used in contact step 2. Therefore, the chloride ion content and the content of each metal ion were not sufficiently reduced. In Comparative Example 5, in contact step 2, two resins were used to fill the column so that the anion exchange resin and the cation exchange resin were in contact. That is, the anion exchange resin and the cation exchange resin were not isolated from each other. Therefore, the chloride ion content was not sufficiently reduced. In addition, with respect to each metal content, the Na ion content was 50 ppb or more and less than 80 ppb. The K ion content, the Ca ion content, and the Fe ion content were 20 ppb or more and less than 50 ppb.
[0139] The above detailed description is for the purpose of illustration and description. In light of the above guidance, many modifications and changes may be made. It is not intended herein to be exhaustive or to limit the subject matter described herein to the precise form disclosed. Although the subject matter has been described in language directed to structural features and / or method actions, it should be understood that the subject matter defined in the appended claims is not necessarily limited to the specific features or acts described above. On the contrary, the specific features and acts described above are disclosed as example forms of implementing the appended claims.
Claims
1. A method for producing an organic sulfonic acid compound, comprising: a reaction step 1, a contact step 2 and a contact step 3, In the reaction step 1, an organic sulfonic acid compound is synthesized using a reaction substrate containing a chlorine compound. In the contacting step 2, the solution of the organic sulfonic acid compound obtained in the reaction step 1 is contacted with an anion exchange resin. In the contact step 3, the solution of the organic sulfonic acid compound after the contact step 2 is contacted with a cation exchange resin, and, The anion exchange resin in the contact step 2 and the cation exchange resin in the contact step 3 are isolated from each other.
2. The method for producing an organic sulfonic acid compound according to claim 1, wherein The organic sulfonic acid compound is a surfactant.
3. The method for producing an organic sulfonic acid compound according to claim 1, wherein In the contact step 2, the solution having an organic sulfonic acid compound concentration of 1 to 50% by mass is contacted with the anion exchange resin.
4. The method for producing an organic sulfonic acid compound according to claim 1, wherein In the contact step 3, the solution having an organic sulfonic acid compound concentration of 1 to 40% by mass is contacted with the cation exchange resin.
5. The method for producing an organic sulfonic acid compound according to claim 1, wherein In the contacting step 2, the solution is heated at a space velocity (SV) of 0.3 to 4.9 h -1 contacting with the anion exchange resin.
6. The method for producing an organic sulfonic acid compound according to claim 1, wherein In the contacting step 3, the solution is heated at a space velocity (SV) of 0.3 to 4.9 h -1 contacting with the cation exchange resin.
Citation Information
Patent Citations
Purification of alkanesulfonic acid
JP2001064249A
Method of treating alkali metal salt of organic sulfonic acid, organic sulfonic acid and surfactant of ammonium organosulfonate type each having reduced concentration of metallic ions
JP2009143842A
Processing method of alkali metal salt and / or ammonium salt of organic sulfonic acid, and production method of organic sulfonic acid ammonium salt type surfactant
JP2015038051A
Molding data generation program and three-dimensional molding system
JP2023178683A